Coal breaking characteristics of high pressure water jet and the law of coordinated pressure relief of slits - Jia, Lianxin; Sun, Zuo; Lu, Junshuai; Gu, Beifang (Frontiers in Earth Science, 2023)
Hydraulic fracturing creates slots on the coal surface through the impact of high-pressure water jets, resulting in stress gradients in the surrounding coal, thereby inducing stress release and increasing gas extraction efficiency. It is an effective measure to prevent coal and gas outbursts. Numerical simulations demonstrate that high-pressure water jets generate slots in the coal, leading to stress gradients in the surrounding coal. These stress gradients drive the coal to move gradually towards the slots, thereby releasing stress. The stress unloading degree in the Y direction is greater than that in the X and Z directions. Damage occurs in the coal near the slots, causing a significant increase in the number of fractures within the coal, which improves gas extraction efficiency. The study reveals the variation in stress unloading of coal between hydraulic fracturing boreholes and extraction boreholes in adjacent positions. By cross-referencing various factors in numerical simulations, the extent of damage in different directions caused by slot formation under different factor combinations is determined. A mathematical model for the range of coal damage surrounding the slots is obtained through MATLAB fitting. The research findings provide references for on-site testing and applications of high-pressure water jet technology.